Why Should I Write a Poem Now : The Letters of Srinivas Rayaprol and William Carlos Williams, 1949-1958 - Williams, William Carlos, 1883-1963 (Book collections on Project MUSE., 2018)
Their intense epistolary relationship between Srinivas Rayaprol and William Carlos Williams, lasting almost a decade and little known up to now, is chronicled in this edition of their letters.